Pemikiran Skeptikal Syiah Terhadap Ahl al-Sunnah wa al-Jama‘ah Dalam Karya-Karya Syiah Melayu: Satu Kritikan (Shi‘ite’s sceptical view towards ahl al-sunnah wa Al-Jamā‘ah in Malay shi‘ite works: A critic) - Mas’od, Mohd Aizam; Hamat, Mohd Fauzi (Department of Aqidah and Islamic Thought, Academy of Islamic Studies, University of Malaya, 2019)
Shi’a has been spread in Malaysia by the 1980s after the Iranian revolution in 1979. In the Malaysian context, dissemination of Shi‘ite to the Malay community occurred through a variety of ways. Among the spreading mediums that had a primary impact were the spread of Malay Shi‘ite works. Various allegations were made about Ahl al-Sunnah wa al-Jamā‘ah in Malay Shi‘ite works to cast doubt on its legitimacy as a school of thought by questioning the argument of Ahl al-Sunnah as being the majority while the majority is not necessarily right. Shi‘ite also claims that the existence of Ahl al-Sunnah wa al-Jamā‘ah has no strong religious and historical basis. Besides, the school raise doubt on the personality of al-Ash‘arі as a former Mu’tazilah figure and accuse Ahl al-Sunnah wa al-Jamā‘ah as having formed a weak alliance between its components from within the school because of different views among themselves in some issues of ‘aqidah and jurisprudence (fiqh). Hence, this article presents critics on the arguments suggested by Shi‘ite in the works. Through the method of documentation in the method of data collection, this study refers to two selected Malay Shi‘ite works entitled Meniti Titian Kebenaran by Khair Izzah and Perempuan Nan Bercinta by Faisal Tehrani. Whereas comparative methods are used in analyzing data by comparing the arguments between Shi‘ite and Ahl al-Sunnah wa al-Jamā‘ah. In general, all these doubts were raised in some of the Malay Shi‘ite works to justify the falsehood of Ahl al-Sunnah wa al-Jamā‘ah’s practice, at the same time establishing Shi‘ite as the only legitimate school of thought. However, the arguments presented in the works were rejected because of the manipulation of facts and scientific treachery. © 2019, University of Malaya. All rights reserved.